Toward Equal Access to Justice: Can Regulating Attorney Fees Ensure Fairness and Broaden Legal Access in Indonesia? - Utami, Nurani Ajeng Tri; Sudrajat, Tedi; Wahyudi, Setya; Pati, Umi Khaerah (Pandecta Research Law Journal, 2024)
In Indonesia, the role of attorneys in resolving legal issues is indispensable, yet the absence of standardized attorney fee regulations has led to significant barriers in accessing legal services. Despite attorneys' rights to receive fees for their services, the lack of clear guidelines has resulted in public perception that hiring legal representation is a luxury, with many unable to afford it. This study explores the urgent need for state regulation of attorney fees to ensure fairness and broaden access to justice for all segments of society. The findings indicate that the lack of fee standardization contributes to inequities in the legal system, creating barriers for lower-income individuals to access legal assistance. Furthermore, it reveals that establishing a clear regulatory framework would provide legal certainty, protect consumers, and promote a more equitable system for all citizens. The novelty of this research lies in its exploration of attorney fees as a critical element in improving access to justice in Indonesia, framing the issue beyond economics and highlighting its social justice implications. By addressing the urgency of regulating attorney fees, the study contributes to the ongoing legal reform discourse, providing policy recommendations for creating a fee structure that balances fairness with professional responsibility. The research emphasizes that deliberative processes, considering factors such as case complexity, impact, and operational costs, should guide the determination of fees. Ultimately, the study presents a compelling argument for rethinking how attorney fees are regulated to ensure that justice is accessible to all, not just the wealthy.